👤

‼️‼️‼️‼️‼️plsss na już‼️‼️‼️‼️​

Plsss Na Już class=

Odpowiedź :

Odpowiedź:

[tex] \frac{(3 - \frac{1}{3} ) \div \frac{4}{3} }{( \frac{1}{3} + \frac{3}{4}) \div (1 - \frac{2}{3} ) + 1 \frac{3}{4} } = \\ \\ = \frac{ \frac{8}{3} \times \frac{3}{4} }{ \frac{13}{12} \div \frac{1}{3} + \frac{7}{4} } = \\ \\ = \frac{ \frac{24}{12} }{ \frac{13}{12} \ \times 3 + \frac{7}{4} } = \\ \\ = 2 \div ( \frac{39}{12} + \frac{7}{4} ) = \\ \\ = 2 \div (\frac{13}{4} + \frac{7}{4} ) = \\ \\ = 2 \div \frac{20}{4} = \\ \\ = 2 \div 5 = \\ \\ = \frac{2}{5} [/tex]